Inorganic Solid Catalyst Derived from Fishbone Waste (Katsuwonus pelamis) for Transesterification of Coconut Oil into Biodiesel - Maisarah, Siti; Ramli*, Muliadi; Maisarah, Minnati Rana; Satrina, Dini; Lubis, Surya; Mitaphonna, Rara; Novita, Desi; Febriani, Febriani (Aceh International Journal of Science and Technology, 2023)
This research has utilized fish bone wastes of tuna (Katsuwonus pelamis) collected at the Lampulo fish market in Banda Aceh. Inorganic oxides have been derived from those fish bone wastes through the decomposition method at high temperatures, namely the calcination process in air atmosphere at 900C for 4 hours. The physicochemical properties of obtained inorganic oxides were characterized using XRD and SEM-EDS techniques. The characterization results indicated that the composition of the calcined fish bone contained hydroxyapatite, CaCO3, and CaO, in which the hydroxyapatite phase has been the major component. Furthermore, the calcination process positively impacts improving the physical morphology and crystalline phase of inorganic oxides. Finally, those obtained inorganic catalysts based on fish bone waste have been applied for transesterifying Coconut oil with methanol, resulting in three main compounds: trimethyl borate, methyl laurate, and methyl octanoate.